1996
DOI: 10.1111/j.1365-2222.1996.tb00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production in children outgrowing hen egg allergy

Abstract: OVA antigen may be capable of inducing a population of Th1-type cells to produce cytokines such as IFN-gamma, resulting in suppression of Th2-type responses, i.e. IL4 secretion. We speculate that the changes in the balance of relevant antigen-induced cytokine synthesis seen in such patients may be causally associated with the improvement in their clinical status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
13
2
Order By: Relevance
“…However, what is less clear is whether the depressed Th1 responses remain depressed during early childhood. Thus, some studies have revealed depressed IFN-γ responses [8], whereas others have shown that IFN-γ responses are increased [9][10][11] in young atopic children compared to their non-atopic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…However, what is less clear is whether the depressed Th1 responses remain depressed during early childhood. Thus, some studies have revealed depressed IFN-γ responses [8], whereas others have shown that IFN-γ responses are increased [9][10][11] in young atopic children compared to their non-atopic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies that determined cytokine production in food antigenstimulated PBMCs showed that patients with food allergy have a T H 2-skewed response compared with nonatopic control subjects. [10][11][12][13][14] In these studies, however, cytokines were measured in bulk cultures of T cells, making it difficult to extrapolate these results to the individual T cell. Food-reactive T H 2 cells have been cloned from blood of patients with food allergy, [15][16][17] but the food-specific Tcell response in food-tolerant subjects has not been evaluated at the clonal level.…”
mentioning
confidence: 99%
“…Shek et al [26] reported that the rate of decrease in food-specific IgE levels over time was predictive for the likelihood of developing tolerance in both milk and egg allergy. Another study reported that the trigger for outgrowing hen egg allergy and peanut allergy may be due to the induction of Th1 type cells to produce IFN-γ resulting in suppression of the Th2 type response [15,18]. Thus, many studies emphasize that long-lasting (Th2 response) IL-4 and IgE levels are vital for the persistence of food allergies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those who remained allergic maintained a Th2-dominated profile [15]. In milk and egg allergy, there are similar reports implicating either Th1/Th2 imbalance or involvement of CD4+ CD25+T regulatory cells in outgrowing clinical sensitivity [16,17,18]. In contrast to these food allergies, the mechanism underlying the persistence of tree nut allergies in general and hazelnut allergy in particular is largely unknown.…”
Section: Introductionmentioning
confidence: 98%